2023
DOI: 10.1021/acs.est.3c00704
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of ZnO Nanoparticles Enhancing Phototransformation of Biologically Derived Organic Phosphorus in Aquatic Environments

Abstract: Zinc oxide nanoparticles (ZnO NPs), as the highly efficient photocatalysts, could enhance the transformation of biogenic organic phosphorus (OP) to orthophosphate (PO 4 3−) by photodegradation, accelerating eutrophication. Conversely, orthophosphate can also transform ZnO NPs and thus potentially alter their catalytic and chemical properties. Here, we investigated the transformation mechanisms of three biogenic OP compounds and ZnO NPs under ultraviolet light (UV) illumination: inositol phosphates (IHPs), nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Techniques such as TEM, XRD, and XPS are commonly used for the characterization of nanomaterials [28,29]. In this study, TEM, XRD, and XPS spectroscopic analyses showed that the size, properties, and structure of the purchased ZnO-NPs were consistent with previously reported findings (Figure 1) [30,31]. Therefore, these results indicate that the purchased materials possess…”
Section: Discussionsupporting
confidence: 90%
“…Techniques such as TEM, XRD, and XPS are commonly used for the characterization of nanomaterials [28,29]. In this study, TEM, XRD, and XPS spectroscopic analyses showed that the size, properties, and structure of the purchased ZnO-NPs were consistent with previously reported findings (Figure 1) [30,31]. Therefore, these results indicate that the purchased materials possess…”
Section: Discussionsupporting
confidence: 90%
“…13−16 In water bodies, phosphonates can be slowly converted to phosphate through enzymatic or photochemical reactions. 17,18 Hence, phosphonates could be a potential source of bioavailable P. Indeed, Sisma-Ventura et al found that the discharge of polyphosphonate-containing desalination brine to coast areas stimulated microbial activity in the seabed. 19 Hasanin et al also reported that phosphonates significantly promote bacterial growth under phosphorus-limiting conditions, thus leading to membrane fouling when used as antiscalants.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that phosphonates cannot be mineralized in WWTPs . Along with their widespread application yet poor degradation in WWTPs, phosphonates are frequently detected in sewage sludge, effluents of WWTPs, lakes, rivers, and oceans. In water bodies, phosphonates can be slowly converted to phosphate through enzymatic or photochemical reactions. , Hence, phosphonates could be a potential source of bioavailable P. Indeed, Sisma-Ventura et al found that the discharge of polyphosphonate-containing desalination brine to coast areas stimulated microbial activity in the seabed . Hasanin et al also reported that phosphonates significantly promote bacterial growth under phosphorus-limiting conditions, thus leading to membrane fouling when used as antiscalants .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In aquatic environments, ZnO NPs have been observed to accelerate the conversion of organic phosphorus (OP) to inorganic phosphorus (IP). 10 This transformation process may facilitate phosphorus (P) utilization by algae, consequently impacting algal growth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sun et al extracted ZnO nanoparticles (ZnO NPs) from commercially available sunscreens and demonstrated their efficacy as photocatalysts for degrading microplastics . ZnO NPs have been detected in aquatic environment at concentrations ranging from ng/L to mg/L, , posing potential risks to ecosystems and human health. , In aquatic environments, ZnO NPs have been observed to accelerate the conversion of organic phosphorus (OP) to inorganic phosphorus (IP) . This transformation process may facilitate phosphorus (P) utilization by algae, consequently impacting algal growth.…”
Section: Introductionmentioning
confidence: 99%